Ibn Qutaiba al-Dīnawarī wa Manhaj al-Ta’wīl fi Fiqhi Mukhtalif al-Hadiṡ wa Āṡāruhu al-‘Ilmiyyah fi al-‘Ālami al-Islāmiyyi wa Indonesia - Ghozali, Abdul Malik (JURNAL JAWI, 2018)
Prophet Tradition (hadith) is the second main source in Islam. Unlike Koran that has completely validated as revelation, while hadith must be examined its validation of transmission and matan. Therefore, problematic hadith appeared, in transmission or matan. Especially, the problematic hadith in wich its matan contradicted, that called ‘musykil al-hadits’ or ‘mukhtalaf al-hadits’. Mukhtalaf al-Hadith, appearly, its matan contradicted with Koran, other equal hadith, axioma or reality. So, Mukhtalaf al-Hadits is more debatable. Mu’tazila who representativeof Rasionalist, rejected existence of mukhtalaf al-hadits as source of religion. Menwhile, Tradisionist (Ahl Hadits) accepted it as source of religion, by condition when its transmission comfirmed/validated. To realease contradiction of mukhtalaf hadits matan, Ibnu Qutayba, one of Muhaddits used rational method; Hermeneutic (Takwil). This research used content analysis method with some approaches; Jurisprudence, Logic, Ushul Fiqh, Theology.